THE USE OF FIGURATIVE LANGUAGE IN MAYBELLINE NEW YORK SLOGAN ADVERTISEMENT - Vanesa Elfiera Agresri Ramadhan (Universitas Negeri Surabaya, 2022)
Figurative language is the language style used by people to communicate. In other words, the figurative language used words to imply another meaning. The benefit of figurative language in this study for the reader was to understand that the theory could be used to provide a clearer and better understanding of the figurative language meaning. This study was conducted to analyze the use of figurative language in the slogan advertisement of Maybelline New York. This study focused on observing the words that contained figurative language using Reaske’s theory (1996). The theory consists of simile, metaphor, metonymy, alliteration, and hyperbole. The method of this study was descriptive qualitative because it described the utterance of the slogans that were categorized into figurative language. At the same time, the data source was taken from the video advertisements of Maybelline New York, which were published on August 2, 2017, to August 30, 2017 on their Official YouTube channel. The result found that the slogan made things more imaginatively appealing. Creative use of figurative language in the advertisement can produce emotionally alive, intellectually appealing, and memorable messages. It is the way of some companies make figurative words as the characteristic for their products or even to describe the company itself in a vision or mission. Buyers will remember this figure of speech as a reference to them that the product supports an individual's movement or goal.